Urgensi Kepesertaan BPJS Kesehatan Sebagai Syarat Peralihan Hak Atas Tanah Berdasarkan Instruksi Presiden Nomor 1 Tahun 2022 Tentang Optimalisasi Pelaksanaan Program Jaminan Kesehatan Nasional - Safitri, Nur Dwi; Fauziyah, Fauziyah (Indonesian Journal Publisher, 2023)
The Health Social Security Implementation Agency (BPJS) is a legal entity formed to administer the Health Insurance program and is directly responsible to the president who has the task of administering National Health Insurance for all Indonesian people. In Presidential Instruction Number 1 of 2022 concerning Optimizing the Implementation of the National Health Insurance Program there is a regulation that authorizes the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency to ensure that every applicant for the transfer of land rights due to buying and selling is an active participant in the Health Insurance Program National (JKN) which is the government's effort to monitor the health conditions of the Indonesian people evenly. The aim of this research is to find out whether the Presidential Instruction is in accordance with Law Number 24 of 2011 concerning Social Security Administering Bodies. The method used in this research is Normative Juridical which examines various formal legal rules such as Laws, using a statutory approach (Statute Approach) and a conceptual approach (Conceptual Approach). In essence, Presidential Instruction No.1 of 2022 is in accordance with Law No.24 of 2011 concerning BPJS and does not violate the main rules in the BPJS Law, however, because the position of the Presidential Instruction is a policy regulation and there are no strict sanctions in it, the Instruction The president may not be implemented because there are no sanctions.